(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Analysis of care outcomes for children under 5 years old with pneumonia and associated factors at Hiep Hoa Medical Center, Bac Giang province, in 2025 Subjects and methods: A cross-sectional descriptive study was conducted on 294 pediatric patients under 5 years old with pneumonia who were receiving treatment at Hiep Hoa Medical Center, Bac Giang province, from January to May 2025. The research instrument consisted of two parts: part A involved collecting patient information from medical records. Part B assessed nursing care activities based on specific criteria using direct observation and a checklist, with a three-point scale: good (2 points), not good (1 point), and not performed (0 points). Care outcomes were considered “meeting expectations” when all of the following conditions were fulfilled: a total care score of ≥ 75% across all care activity groups; the child was discharged in stable condition within 10 days of hospitalization; the caregiver reported being satisfied or very satisfied with the nursing care provided. Results: Children under 1 year of age accounted for 42.8%, while those aged 1-5 years accounted for 57.2%; the proportion of boys was 58.5% and girls 41.5%. Among the pediatric patients, 4.1% had a history of preterm birth and low birth weight; 8.2% were malnourished; 64.6% had a history of previous pneumonia; 85.6% presented with fever; 99% had tachypnea; 18% exhibited chest indrawing; 17.7% had respiratory distress; and 13% were diagnosed with severe pneumonia. High levels of performance were recorded in several areas of care: routine care for children with pneumonia reached 93.9%; monitoring and detection of complications was 98.6%; other aspects of comprehensive care reached 94.6%; and counseling services were provided in 92.9% of cases. Overall, 85% of care outcomes met expectations, while 15% did not. Factors found to be significantly associated with care outcomes included: preterm birth (OR = 4.40; p = 0.008), respiratory distress (OR = 2.54; p = 0.016), and severe pneumonia (OR = 2.75; p = 0.009). Thực hiện tốt trong chăm sóc thường quy trẻ viêm phổi đạt 93,9%; theo dõi và phát hiện biến chứng 98,6%; chăm sóc toàn diện khác 94,6%; tư vấn 92,9%. Conclusion: Care outcomes met expectations in 85% of pediatric patients, while 15% did not meet expectations. Several factors associated with suboptimal care outcomes included a history of preterm birth and low birth weight, current malnutrition, presence of respiratory distress upon hospital admission, and a diagnosis of severe pneumonia.